Analisis Perpol Nomor 10 Tahun 2025 Penempatan Anggota Polri Luar Struktur Dalam Perspektif Kode Etik: Analysis of Police Regulation No. 10 of 2025 on the Placement of Police Officers Outside the Structure in the Perspective of the Code of Ethics - Sobirin, Lisda Apriliani (Jurnal Media Hukum, 2026)
This study aims to analyze Police Regulation Number 10 of 2025 concerning the placement of POLRI members outside the organizational structure from the perspective of professional code of ethics. The research method used is normative juridical with a literature study approach to primary and secondary legal materials. The results show that Perpol 10/2025 provides legal certainty for the technical assignment of POLRI members in 17 ministries/institutions, but there are still weaknesses in ethical oversight aspects. The regulation does not yet explicitly regulate ethical oversight mechanisms, ethical accountability, and coordination between POLRI and recipient institutions. From the perspective of the professional code of ethics, placing POLRI members outside the structure has the potential to create conflicts of interest and threaten the principles of neutrality, integrity, and institutional accountability. Perpol 10/2025 requires strengthening of more transparent and accountable ethical oversight mechanisms to ensure that assignments outside the structure do not diminish POLRI's credibility as a law enforcement institution.